2018
DOI: 10.1155/2018/9856537
|View full text |Cite
|
Sign up to set email alerts
|

A Security Sandbox Approach of Android Based on Hook Mechanism

Abstract: As the most widely applied mobile operating system for smartphones, Android is challenged by fast growing security problems, which are caused by malicious applications. Behaviors of malicious applications have become more and more inconspicuous, which largely increase the difficulties of security detection. This paper provides a new security sandbox approach of Android based on hook mechanism, to further enrich Android malware detection technologies. This new sandbox monitors the behaviors of target applicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Android is an open source Linux-based operating system (OS) that allows users to manage activities of daily living (ADL) [39]. Android OS is based on security-enhanced Linux (SE-Linux) that emphasizes security controls in the Android infrastructure by maintaining a sophisticated set of rules, Linux policies, and a kernel-level application sandboxing mechanism [40]. Additionally, SE-Linux assigns identification numbers (ID) to users and groups that identify and limit users, processes, and application access to kernel level and hardware attributes [32].…”
Section: Android Open Source Project (Aosp)mentioning
confidence: 99%
“…Android is an open source Linux-based operating system (OS) that allows users to manage activities of daily living (ADL) [39]. Android OS is based on security-enhanced Linux (SE-Linux) that emphasizes security controls in the Android infrastructure by maintaining a sophisticated set of rules, Linux policies, and a kernel-level application sandboxing mechanism [40]. Additionally, SE-Linux assigns identification numbers (ID) to users and groups that identify and limit users, processes, and application access to kernel level and hardware attributes [32].…”
Section: Android Open Source Project (Aosp)mentioning
confidence: 99%
“…Later, with the development of technology of dynamic test, followed much research that involved obtaining target data when the application is running on Android, like Mobile-sandbox [17]. It can obtain the target data by hooking the underlying function of the application.…”
Section: Encrypted Files Recoverymentioning
confidence: 99%
“…It can obtain the target data by hooking the underlying function of the application. Research recovered encrypted files on PC by means of using sandbox [17] to hook the underlying function of ransomwares and obtain encryption keys. Then encrypted files can be decrypted with encryption keys.…”
Section: Encrypted Files Recoverymentioning
confidence: 99%
“…Furthermore, this paper implemented the proposed method on five nodes, and the experimental results confirmed that block chain-based authentication can decrease the authentication delay in multi-hop environment that makes the packet loss rate larger. Note that mining data from multiple data sources to extract useful information [Wang, Ji, Liu et al (2018)] for better understanding of security risk evaluation should be considered in the future study, and it is also important to analyze the behaviors of target application [Jiang, Liu, Yang et al (2018)] running on mesh nodes.…”
Section: Introductionmentioning
confidence: 99%